PENGARUH EARNING POWER DAN DIVERSIFIKASI USAHA TERHADAP PRAKTIK MANAJEMEN LABA - Elmi Elmi; Tatik Zulaika; Leliana Maria Angela (KOLONI, 2022)
This study aims to determine the effect of earning power and business diversification on earnings management practices as measured by discretionary accruals. Population of this research are 35 non-cyclical consumer manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. Using the method purposive sampling obtained as many as 28 samples. Data analysis technique used multiple linear regression SPSS version 24. Multiple linear regression used to measure the strength of the relationship and the direction of independent variables to dependent variable. The results of the search showed that partially, earning power had a positive and significant effect to earnings management practices, while variables business diversification, had no significant to earnings management practices. Keywords: Earnings Management, Earning power and Business Diversification